2020
DOI: 10.1107/s2053230x20011073
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Moco carrier protein fromRippkaea orientalis

Abstract: The molybdenum cofactor (Moco) is the prosthetic group of all molybdenum-dependent enzymes except for nitrogenase. The multistep biosynthesis pathway of Moco and its function in molybdenum-dependent enzymes are already well understood. The mechanisms of Moco transfer, storage and insertion, on the other hand, are not. In the cell, Moco is usually not found in its free form and remains bound to proteins because of its sensitivity to oxidation. The green alga Chlamydomonas reinhardtii harbors a Moco carrier prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
2
10
1
Order By: Relevance
“…states that were published for C. reinhardtii MCP [13] and R. orientalis MCP [22]. SAXS confirmed that notion of a V. carteri MCP tetramer.…”
Section: The Oligomeric State Of V Carteri Mcpsupporting
confidence: 75%
See 4 more Smart Citations
“…states that were published for C. reinhardtii MCP [13] and R. orientalis MCP [22]. SAXS confirmed that notion of a V. carteri MCP tetramer.…”
Section: The Oligomeric State Of V Carteri Mcpsupporting
confidence: 75%
“…The amino acid sequence comparison (Figure 1A) of eukaryotic MCPs revealed a region of low sequence homology (LHR) located in the N-terminal part of the protein sequence. Results of docking experiments published for C. reinhardtii MCP [13] as well as a bacterial MCP from R. orientalis [22] indicate that Moco binding probably occurs in a predominantly positively charged crevice that is located in proximity to the LHR. We therefore investigated the LHR's role by creating a chimeric V. carteri MCP, which had its endogenous LHR switched for its counterpart from R. orientalis MCP (Figure 6A).…”
Section: Moco Binding To V Carteri Mcpmentioning
confidence: 99%
See 3 more Smart Citations